Confirmation of Acer campestre (Sapindaceae) presence in Algeria and new sites records - Chikhaoui, Zakia; Said, Samir Ait; Laidi, Keyssa; Krouchi, Fazia (Phytotaxa, 2024)
The presence of Acer campestre in Algeria is confirmed and its distribution updated by recording five new occurrences. A morphological description of leaves, shoots, and samaras is provided, based on samples collected from several occurrence sites.